Influence of solvent on the morphology and photocatalytic properties of ZnS decorated CeO2 nanoparticles - Raubach, Cristiane W.; Polastro, Lisanias; Ferrer, Mateus M.; Perrin, Andre; Perrin, Christiane; Albuquerque, Anderson R. [UNESP]; Buzolin, Prescila G. C. [UNESP]; Sambrano, Julio R. [UNESP]; Santana, Yuri B. V. de [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (American Institute of Physics (AIP), 2014)
Herein, we report a theoretical and experimental study on the photocatalytic activity of CeO2 ZnS, and ZnS decorated CeO2 nanoparticles prepared by a microwave-assisted solvothermal method. Theoretical models were established to analyze electron transitions primarily at the interface between CeO2 and ZnS. As observed, the particle morphology strongly influenced the photocatalytic degradation of organic dye Rhodamine B. A model was proposed to rationalize the photocatalytic behavior of the prepared decorated systems taking into account different extrinsic and intrinsic defect distributions, including order-disorder effects at interfacial and intra-facial regions, and vacancy concentration. (C) 2014 AIP Publishing LLC.